Pengaruh Metode Cooperatif Learning dan Motivasi Belajar Siswa Pada Mata Pelajaran PAI di SMP Buana Sidoarjo - Afifah (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Education is a system consisting of several interconnected components, including learning achieved from the material taught, the media used, the curriculum situation, the management of teaching and learning processes and evaluation. In order to increase the students' affectivity, teachers must always try with various strategies, including by using learning models to generate student learning activities by changing monotonous learning activities. One way is to apply the Cooperative Learning method. This study uses quantitative descriptive research, with methods of observation, questionnaires and documentation. The Cooperative Learning method is classified as good obtained with 79.5% results, for students 'learning motivation is classified as good obtained with 77.3% results, the effect of cooperative leraning method on students' motivation to learn high is evidenced from rxy = 0.82, which is between 0.800- 1,00